The Implications of Child Maltreatment, a Subjective Maternal Perspective from Cape Town - Adams, Kirsten (The IIE, 2020)
This study aims to gain an understating about the maternal perspective of childhood maltreatment and the implications thereof in Cape Town. The African Network for the Prevention and Protection Against Child Abuse and Neglect (ANPPCAN) describes child maltreatment as “the intentional, unintentional or well intentional acts that endanger the physical, health, emotional, moral and the educational welfare of the child.” According to Artz, Burton, Leoschut & Ward (2015) 1 in 5 teenagers reported experiencing sexual abuse, 1 in 3 teenagers experiencing physical abuse, 16.1% of teenagers experiencing emotional abuse and one fifth of teenagers experiencing neglect (a non-physical form of maltreatment). To address this topic, Erikson’s theory of the psychosocial development was used in line with a qualitative research approach. This ensured that rich data was collected by means of semi-structured interviews with five mothers from Cape Town. The key themes that emerged was defining child maltreatment, awareness of child maltreatment and the implications thereof, and the under-reporting of child maltreatment. This study contributes to the body literature by providing a maternal insight into the happenings of child maltreatment.
Keywords: Maternal perspectives; Child maltreatment; Implications of maltreatment